Multidisciplinary, Multilingual, Multilevel and Multipurpose Usage of GeoGebra Software in Education - Jancheski, Metodija; Jancheska, Sofija (My University, 2019)
The technical characteristics of GeoGebra have been examined, its various views and tools have been described, with special emphasis on interactive tools. The use of GeoGebra in education has been depicted, mainly in mathematics. We emphasized the importance of sharing GeoGebra digital learning materials within the GeoGebra community, which is present and active in more than 190 countries now and is growing astonishingly fast. In this context, various forms of organizing GeoGebra digital learning materials are reviewed: GeoGebra Materials, GeoGebra Wiki, GeoGebra Tube, GeoGebra Books and GeoGebra Exercises. The author demonstrates the universal and effective application of the GeoGebra software in four dimensions. First, GeoGebra can be applied in a variety of disciplines, primarily in mathematics and computer science, and in subjects in the field of natural and technical sciences. Second, the use of GeoGebra also covers a wide range of applications, from primary education to higher education. Third, GeoGebra enables the creation of multilingual digital learning content. Finally, various variations of animations and simulations with different weights can be made in GeoGebra, which can enhance the individualization of teaching within multiple levels of education and enable conditions for programmed instruction. A detailed overview of three conducted researches and the obtained results are provided. The researches include filling in questionnaires by teachers and students, as well as performing teaching lessons in Mathematics and Physics in two secondary schools with students divided into experimental groups (where GeoGebra animations and simulations were applied) and control groups (where the classes were held in classical, traditional way, without the use of educational software). According to our researches and observations, free and open-source software like GeoGebra is a great opportunity that should be used to the fullest extent in our education especially in the conditions of obvious need for educational software and digital educational materials, corresponding to our education curricula. In the concluding observations, we give concrete conclusions, suggestions and recommendations for implementing GeoGebra in the educational system.
Keywords: GeoGebra, application of GeoGebra in education, free and open educational software